Migraine masquerading as temporomandibular disorders: a case report / Yoshinobu Shoji and Harold V Cohen. - Yoshinobu, Shoji; Harold, V Cohen (Universiti Teknologi MARA Cawangan Selangor, 2018)
Migraine is a common disabling primary headache disorder. Ipsilateral radiation of pain to orofacial regions, including teeth, jaws and temporomandibular joints, although not a common complaint, could occur. The area of involvement may obscure the diagnosis and lead to unnecessary dental treatment. A case is presented in which a patient initially sought dental care for left jaw pain that radiated to her left maxillary teeth and temple region and she was also experiencing discomfort in the left masticatory musculature. Subsequently a medical consult diagnosed migraine headache without aura and fortunately unnecessary dental treatment was not done. The key issue here is the complexity of the Trigeminal nerve when the dentist is assessing a patient for dental or other orofacial pain complaints and dental pathology has been ruled out. Equally as important is the dentist taking thorough medical history since a patient may not tell a dentist about a “headache” because the pain is in the teeth and/or jaws. And, perhaps most important is the final differential diagnosis whether made by the dentist or medical care provider.